Short-term ketamine use in bipolar depression: a review of the evidence for short-term treatment management - Wilkowska, Alina; Cubała, Wiesław Jerzy (Frontiers in Psychiatry, 2023)
Bipolar depression constitutes a major problem in psychiatry. It correlates with high suicidality, treatment resistance, chronicity, and poor quality of life. Registered treatment for bipolar depression is limited and insufficient. There is an urgent need for implementing new therapeutic strategies. Intranasal ketamine’s enantiomer—esketamine is a novel rapid-acting antidepressant with proven efficacy in treatment-resistant depression. Research on bipolar depression, although not as comprehensive, indicates that it may be a viable and safe substitute with minimal risk for mood polarity changes. Reports suggest that ketamine treatment in bipolar depression may reduce suicidal tendencies, decrease anhedonia, and alleviate anxiety. Ketamine’s mood-stabilizing properties are also hypothesized. In this narrative review, we focus on ketamine use as an add-on to standard medication for the acute treatment of bipolar depression.